Spinal cord injury as a trigger to develop periodic leg movements during sleep: an evolutionary perspective - Susana Cristina Lerosa Telles; Rosana S. Cardoso Alves; Gerson Chadi (Arquivos de Neuro-Psiquiatria)
The primary trigger to periodic limb movement (PLM) during sleep is still unknown. Its association with the restless legs syndrome (RLS) is established in humans and was reported in spinal cord injury (SCI) patients classified by the American Spinal Injury Association (ASIA) as A. Its pathogenesis has not been completely unraveled, though recent advances might enhance our knowledge about those malfunctions. PLM association with central pattern generator (CPG) is one of the possible pathologic mechanisms involved. This article reviewed the advances in PLM and RLS genetics, the evolution of CPG functioning, and the neurotransmitters involved in CPG, PLM and RLS. We have proposed that SCI might be a trigger to develop PLM.